A REVIEW ON- PREPARATION OF BIO PLASTICS FROM AGRI-WASTE - Animesh Biswas,; Srijani Pal,; Rupali Dhara Mitra, (The Bioscan, 2024)
The whole earth is now submerged with plastics, a non-biodegradable substance. It is one of the major environmental hazards now-a-days. Today the entire world is in search of new product development from waste agri-products. In this article an attempt has been made to determine the different optimized method parameters for the preparation of bioplastics from waste agri products. Bioplastics can be fabricated from different food waste like pumpkin skin, cucumber skin, banana peel, apple peel, pomegranate and brinjal peel etc. Bioplastics are biodegradable polymer that can be utilized by microbes as waste treatment technique may be a solution to the problem of plastic pollution in near future around the world. These bioplastics can be utilized in biomedical industry as capsule film; can be a substitute of plastic bags, cosmetic applications, storage utensils, bio-based cutlery and table ware. Non-toxic biodegradable plastics can be used as sutures in heart operations etc.